Sistem Informasi Kartu Tanda Mahasiswa (KTM) Menggunakan Kodular Berbasis Android Pada Stmik Indonesia Banda Aceh - Fikri, Muhammad; Ahmad, Lukman; Imilda (Jurnal Sistem Komputer (SISKOM), 2023)
In the era of rapid development of digital information technology, the presence of information systems is crucial, especially in an educational context such as at STMIK Indonesia Banda Aceh. In the midst of demands for efficient services for students, the process of making a Student Identity Card (KTM) often takes quite a long time. To overcome this challenge, this research proposes implementing QR code technology on KTM as a solution. Through the implementation of an Android application using the Kodular platform, this system enables the student identification and verification process to be faster and more effective. The results of system testing show that KTM creation can be done via an Android smartphone. It is hoped that the implementation of this system can help speed up and simplify the administration process for staff and students, as well as all parties involved in managing KTM data.